Aplication of Quantitative and Qualitative Methods in Risk Management of Credit Portfolio in the Conditions of the Banking System of the Republic of Tajikistan - Isupova, Basgul Fajzullohonovna (Olsztyn Economic Journal, 2013)
In this article, an analysis of the fundamental methods of risk assessment and risk management of credit portfolio is conducted. In particular, complex and qualitative methods of risk management of credit portfolio studied in details, namely analytical, statistical and coefficient methods. Based on the coefficient method the author proposes a number of standards for the assessment of potential losses in credit activity.